Rhythm and rate control of atrial fibrillation in the emergency department – A large community-based observational study. Issue 6 (5th December 2017) - Gilbert, Cameron J.; Angaran, Paul; Mariano, Zana; Aves, Theresa; Dorian, Paul
Abstract: Objective: Atrial fibrillation (AF) is the most common arrhythmia presentation to the emergency department (ED) and frequently results in admission to the hospital. Although rarely life-threatening and not usually an emergent condition, AF places a large burden on our health-care system. The objective of this study was to describe the practices of ED physicians in the management of AF in a large urban Canadian city. Methods: From January 1, 2010 to December 31, 2010, patients with a primary diagnosis of AF were identified across 10 EDs in Toronto, Canada (N=2, 609). Fifty patients were selected at random from each hospital for a detailed chart review (n=500). Results: Two hundred thirty-two patients (46%) received rate control, and 129 (26%) received rhythm control with the remainder (28%) receiving neither therapy. Sixty-seven percent of patients were discharged home. Most patients (79%) were symptomatic on arrival; however, only a minority of these (31%) received rhythm control. Factors that were associated with rhythm control included younger age, duration of palpitations ≤ 48 hours, a lower CHADS2 score, and the absence of left ventricular dysfunction. Conclusion: Our data suggest a wide range of practice amongst ED physicians treating patients presenting to the ED with a primary diagnosis of AF. A randomized trial is needed to better understand the optimal management strategy in this patient population and setting. RÉSUMÉ: Contexte: La fibrillation auriculaire (FA) est le trouble du rythme cardiaque le plus fréquent traité au service des urgences (SU) et il se solde souvent par l'hospitalisation. Il met rarement la vie en danger et ne nécessite généralement pas de soins très urgents, mais il impose un lourd fardeau au système de soins de santé. L'étude avait donc pour but de décrire les pratiques en matière de prise en charge de la FA au SU, dans un grand centre urbain, au Canada. Méthode: Du 1 er janvier 2010 au 31 décembre 2010, un diagnostic principal de FA a été posé chez des patients traités dans 10 SU (n=2609), à Toronto (Canada). Parmi ceux-ci, 50 ont été sélectionnés au hasard dans chaque hôpital en vue d'un examen détaillé des dossiers (n=500). Résultats: Deux cent trente-deux patients (46 %) ont été soumis à un traitement de maîtrise de la fréquence; 129 (26 %), à un traitement de maîtrise du rythme, et les autres (28 %), à aucun de ces traitements. Soixante-sept pour cent des patients ont pu retourner à domicile. La plupart des malades (79 %) présentaient des symptômes à l'arrivée, mais seule une minorité d'entre eux (31 %) a été soumise à un traitement de maîtrise du rythme. Les facteurs associés à la maîtrise du rythme comprenaient le jeune âge, une durée des palpitations ≤48 heures, un faible score CHADS2 et l'absence de dysfonctionnement du ventricule gauche. Conclusions: Les données recueillies laissent entrevoir l'existence d'un large éventail de pratiques dans le traitement de la FA posé comme diagnostic principal au SU. Il faudrait mener un essai à répartition aléatoire afin de mieux comprendre la stratégie de prise en charge optimale de la FA, au SU, dans ce groupe particulier de patients.